The power of the imagination to affect peripersonal space representations. Issue 3 (16th March 2018) - Davoli, Christopher C.; Bloesch, Emily K.; Abrams, Richard A.
ABSTRACT: It is known that visual processing is altered for objects near the hands as well as for objects near the imagined position of the hands, indicating that the imagination can be used to remap peri-hand space. Little is known, however, about the physical conditions that allow for this remapping. In the present study, participants in one experiment performed visual searches through displays that were beyond reach while imagining that their hands were near the display. This imagined impossible posture slowed visual search rates, showing that imagination effectively remapped peri-hand space to be near the display. In another experiment, participants searched displays they were holding, but sometimes imagined their hands to be far away. This produced faster search rates, revealing a remapping of peri-hand space away from the monitor. The results provide new insights into the mechanisms involved in the representation of peri-hand space and about the power of imagined actions to influence body representations.